If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3z + 1) + -1(2 + -6) = 0 Reorder the terms: 2(1 + 3z) + -1(2 + -6) = 0 (1 * 2 + 3z * 2) + -1(2 + -6) = 0 (2 + 6z) + -1(2 + -6) = 0 Combine like terms: 2 + -6 = -4 2 + 6z + -1(-4) = 0 Multiply -1 * -4 2 + 6z + 4 = 0 Reorder the terms: 2 + 4 + 6z = 0 Combine like terms: 2 + 4 = 6 6 + 6z = 0 Solving 6 + 6z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6z = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 6z = 0 + -6 6z = 0 + -6 Combine like terms: 0 + -6 = -6 6z = -6 Divide each side by '6'. z = -1 Simplifying z = -1
| f(0.03)=3x^3-2x^2+6x-4 | | a=(5x-3)(x+2)(2x+3)(3x-2) | | 7-4x=x-8 | | -6+7x=6x-6 | | 2w+w+2w+1=76 | | sin(180)= | | 15.1r=8.9 | | 3p^2-17=0 | | a=(5x-3)(x+2) | | 3x^2+2x=2x+27 | | 4a-3=2a+9 | | 2x^2+3-3=0 | | 8+3x=-3x-4 | | 15x-5+13x+13=180 | | 2(y-7)=5y-32 | | 2(5t-2)=20-(2t) | | 3xwhat=54 | | -2u+12=2(u+4) | | 12t=30 | | 15x-5+14x+4=180 | | -7+x=-5x+29 | | 6(v-6)=9v-33 | | 3d+14=19 | | (4x-15)+5x=30 | | 13x+169=0 | | u=3(7n+34)+7(n+1) | | 1X+4=4X-10 | | 5[20+p]=2[30+p] | | 4x+5=27-7x | | 8x-3=4y+16 | | 32-(3x-2(2x-3))=183 | | 40-4(x-3)=7x-5 |